Intensive Rehabilitation Treatment in Parkinsonian Patients with Dyskinesias: A Preliminary Study with 6-Month Followup - Giuseppe Frazzitta; Micaela Morelli; Gabriella Bertotti; Guido Felicetti; Gianni Pezzoli; Roberto Maestri (Parkinson's Disease)
A major adverse effect of levodopa therapy is the development of dyskinesia, which affects 30–40% of chronically treated Parkinsonian patients. We hypothesized that our rehabilitation protocol might allow a reduction in levodopa dosage without worsening motor performances, thus reducing frequency and severity of dyskinesias. Ten Parkinsonian patients underwent a 4-week intensive rehabilitation treatment (IRT). Patients were evaluated at baseline, at the end of the rehabilitation treatment and at 6-month followup. Outcome measures were the Unified Parkinson’s Disease Rating Scale Sections II, III, and IV (UPDRS II, III, IV) and the Abnormal Involuntary Movement Scale (AIMS). At the end of the IRT, levodopa dosage was significantly reduced (P=0.0035), passing from 1016±327 to 777±333 mg/day. All outcome variables improved significantly (P<0.0005 all) by the end of IRT. At followup, all variables still maintained better values with respect to admission (P<0.02 all). In particular AIMS score improved passing from 11.90±6.5 at admission to 3.10±2.3 at discharge and to 4.20±2.7 at followup. Our results suggest that it is possible to act on dyskinesias in Parkinsonian patients with properly designed rehabilitation protocols. Intensive rehabilitation treatment, whose acute beneficial effects are maintained over time, might be considered a valid noninvasive therapeutic support for Parkinsonian patients suffering from diskinesia, allowing a reduction in drugs dosage and related adverse effects.